PELATIHAN PEMBENTUKAN SISTEM PENGADUAN DAN KOTAK SARAN DARI MASYARAKAT UNTUK MENINGKATKAN KINERJA DESA - Deswinda Ayu Pertiwi; Tuti Sulastri; Diana Fajarwati (Universitas Islam 45 Bekasi, 2023)
Installation of suggestion boxes in public service offices in Indonesia is regulated in the Presidential Regulation of the Republic of Indonesia No. 76 of 2013 concerning public service complaints. The same thing is also stated in Law Number 25 of 2009 concerning public services, in this case referred to as a complaint box. The research method used is counseling, implementation, and evaluation. The data collection technique is by observation. The results showed that the suggestion box complaint service mechanism, namely the lack of socialization between the RT head and the surrounding community, therefore the authors wanted to form a suggestion box to convey aspirations from the community to improve the performance of the local RT, then it could be implemented again after the author left the community service location in the village. Bantarsari. The supporting factor is the mechanism with community participation in supporting the formation of the complaint system and the suggestion box, while the inhibiting factor is that there are still many people who do not realize the importance of the existence of the suggestion box.